Increase of the steel 45L characteristics - S. N. Primerov; V. V. Velmisov; N. N. Kiseleva; E. G. Shwarts; V. P. Meshcheijakov; A. N. Karasj (Литьë и металлургия)
Тhе results, given in the article, are an evidence of a prospect of application of ligature AKTse at production of castings from steel 45 L for tractors MTZ-1221.